Analisis Faktor-faktor Kritis yang Memengaruhi Kesuksesan Agripreneur di Tengah Transformasi Ekonomi Digital - Putri, Dessy Iriani; Meisanti, Meisanti; Sukrianto, Sukrianto; Zakiah, Nurul; Grahito, Damar (Universitas Galuh, 2026)
The rapid evolution of digital technologies has reshaped the agricultural sector, offering new opportunities for innovation and sustainability. In Indonesia, agripreneurs are emerging as key agents in modernizing agriculture. This study aims to identify critical factors influencing the success of young agripreneurs in the digital era. Employing a quantitative approach, the stufy utilized Structural Equation Modeling–Partial Least Squares (SEM-PLS) with data collected from 30 young and successful agripreneurs across various regions in Indonesia. The model examined three exogenous constructs, human capital, social capital, and technology, and one endogenous construct, agripreneurial success. Findings reveal that the majority of agripreneurs belong to Generation Z (59.09%), characterized by high digital literacy and adaptability to new technologies. The average annual income of participants was approximately IDR 165 million, consistent with small to medium scale enterprises. SEM-PLS results demonstrate that only technology has a significant and positive effect on agripreneurial success (β = 0.615; p < 0.01), while human capital and social capital show no statistically significant influence. Measurement model assessments confirmed strong reliability and validity of the constructs, with all composite reliability and AVE values meeting recommended thresholds. These findings underscore the transformative role of technology in shaping agribusiness outcomes, highlighting the need for targeted policy interventions that support digital literacy, infrastructure development, and innovation. Although traditional success factors like education and networking were not significant in this model, their practical value remains important for long-term sustainability. The study offers strategic insights for enhancing digital transformation and promoting sustainable agripreneurship among Indonesia’s youth.